Implications of form postponement to manufacturing: a case study - Skipworth, Heather; Harrison, Alan (Taylor & Francis, 2004)
Postponement is an approach that helps to deliver more responsive supply chains. Form postponement involves the delay of final manufacturing until a customer order is received and is commonly regarded as an approach to mass customization. However, while much is written in the literature about the benefits and strategic impact of form postponement, little is still known about its application. This paper addresses how form postponement was applied in terms of its operational implications within a manufacturing facility through a retrospective study that tracked implementation of form postponement in a manufacturer of specialist high-voltage cabling equipment, called here 'ElectriCo'. The operational measures for products selected for form postponement were compared with those for products that continued to be made under make-to-order and make-to-stock regimes. Propositions were tested that addressed the operational implications of form postponement within the manufacturing facility, the impact of form postponement on selected performance metrics, and the demand profile for which form postponement was the preferred regime. Multiple data collection methods were used whereby documentary, archival and database evidence were used to measure operational characteristics across a broad front. The findings show that form postponement improved responsiveness but did not necessarily improve delivery reliability. The extent to which the order lead time can be reduced is dependent not only on the responsiveness of the postponed process, but also crucially on the responsiveness of the planning system. It was found that the problem of adapting the manufacturing planning and production scheduling systems at ElectriCo had been underestimated. This and other problems subsequently undermined the form postponement application and led to its eventual abandonment. The authors are undertaking further research of form postponement applications in different production contexts to provide further evidence for its operational implications.
Keywords: Form postponement; Responsiveness; Customization; Decoupling point